1997
DOI: 10.1021/ja964163s
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Vapor Deposition of Aluminum Nitride:  Unusual Cluster Formation in the Gas Phase

Abstract: An ab initio investigation of the chemical vapor deposition of AlN from the AlCl3NH3 adduct is presented. Geometries, harmonic vibrational frequencies and relative energies for the AlCl3NH3 adduct, its dissociation products AlCl n , NH n (n = 1−3), and ring and cluster compounds [(Cl2AlNH2) n (n = 1, 2), (ClAlNH) n (n = 1, 2, 3, 4, 6)] are discussed. The Al−N bond lengths in the investigated compounds are strongly dependent on the coordination numbers of the aluminum and nitrogen centers, decreasing from 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
92
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 62 publications
10
92
1
Order By: Relevance
“…For example, Langho et al [19] calculated that the ground state of AlN is 3 P, using the complete-active-space self-consistent-®eld (CASSCF) [22] and multi-reference con®guration interaction (MRCI) methods. Their assignment has been in accord with experimental observation and later calculations [20,21]. Langho et al showed that the adiabatic excitation energy (T e ) for the 3 S A ®rst excited state of AlN is less than 0.1 eV, where its energetic separation depends on the level of theory.…”
Section: Introductionsupporting
confidence: 68%
“…For example, Langho et al [19] calculated that the ground state of AlN is 3 P, using the complete-active-space self-consistent-®eld (CASSCF) [22] and multi-reference con®guration interaction (MRCI) methods. Their assignment has been in accord with experimental observation and later calculations [20,21]. Langho et al showed that the adiabatic excitation energy (T e ) for the 3 S A ®rst excited state of AlN is less than 0.1 eV, where its energetic separation depends on the level of theory.…”
Section: Introductionsupporting
confidence: 68%
“…In fact, the AlCl 3 and NH 3 molecules can form a monoamine adduct even at room temperature that dissociates at about 700 C. The AlCl 3 and NH 3 molecules can also form a long line of other adducts with structures from dimers to hexagons with increasing stability [7]. Keeping the reactants separated as long as possible would help prevent the unwanted gas phase reactions but this also has a problem.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of AlCl 3 2NH 3 in the gas phase as shown in Eq. (2) is desirable due to its clean and relatively well-understood decomposition to AlN [7]. Additionally, the aluminum chloride-alkyl amine lets AlCl 3 2NH 3 decompose much later thus providing a better carrier which reduces the chance of formation of the lower temperature adducts.…”
Section: Discussionmentioning
confidence: 99%
“…The InCl 3 forms an ammonia adduct (Cl 3 In:NH 3 ) with NH 3 and the subsequent monomer formation (Cl 2 InNH 2 ) via a HCl elimination leads to the formation of innate In-N bond in monomer [18][19][20][21][22]. The oligomer species ([Cl 2 InNH 2 ] n ), an aggregate of monomers, has been identified to be stable in the gas phase below a certain high temperature (up to 1000 K) [18][19][20][21][22]. The strong intramolecular H-Cl hydrogen bonding and dipoledipole interactions are known to favor the formation of larger oligomer species [21].…”
Section: Methodsmentioning
confidence: 99%